Sustainable transport and tourism destinations - Zamparini, Luca (Emerald Publishing, 2021)
Transport and sustainability are intrinsically linked. This book examines the links between transport, tourism, and sustainability by means of a series of large case studies covering several countries
Keywords: Transport; Mobilität; Nachhaltigkeit; Öffentlicher Personennahverkehr; Tourismus; Transportation / Environmental aspects; Sustainable tourism; Electronic books